Validation of an educational game about first aid for schoolchildren - Bárbara Duarte Dutra; Keyla Cristiane do Nascimento; Maria Elena Echevarría-Guanilo; Valéria de Cássia Sparapani; Gabriela Marcellino de Melo Lanzoni (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to validate the content and appearance of an educational game about first aid for schoolchildren with experts in education and health. Methods: this is a methodological, quantitative and descriptive research, carried out using the Delphi technique, using an online collection instrument, covering 55 items of the game. Content and appearance assessment was performed by 26 judges. The data were analyzed using Content Validity index. Results: the final prototype is presented in a board format, composed of four buildable pawns and 117 cards between questions, alerts and challenges. Overall Content Validity index of 0.95 and greater than 0.8 was obtained for all items in two Delphi rounds. Conclusions: the educational game validated by experts is a pedagogical tool for teaching first aid to schoolchildren as an option to traditional educational practices.